PENGARUH KUALITAS PRODUK, CITRA RASA, DAN PROMOSI TERHADAP MINAT BELI KUE BAY TAT (Studi Kasus Pada Konsumen Kue Bay Tat di Kelurahan Pematang Gubernur Kota Bengkulu) - Iqbal, Muhammad; Arini, Eti (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This research is motivated by the results of observations and interviews with the author in one of the research samples, that the object under study has interesting problems to study. The problem in this study is whether product quality, taste image, and promotion affect purchase intention. The purpose of this study is to determine the effect of product quality, taste image, and promotion on buying interest in traditional bay tat cakes for consumers of bay tat cakes in the village. Pematang Governor of Bengkulu City, this study used qualitative research methods, the samples examined in this study totaled 100 people and the sampling used the incidental sampling method, the data collection method used observation and questionnaires, the data analysis method used was instrument test. This research uses validity test, reliability test, classical assumption test, multiple linear regression test, coefficient of determination test (R2) followed by hypothesis testing. Based on the multiple linear results obtained for the regression equation Y = 1.561 - 0.020X1 + 0.678X2 + 0.546 X3 the research results show the value of the coefficient of determination shows the value of R² = 0.706. The results of the research and the hypothesis show that Product Quality (X1) does not have a significant influence on Purchase Intention, Citra Rasa (X2) has a positive and significant effect on Purchase Intention, Promotion (X3) has a positive and significant effect on Purchase Intention, Product Quality (X1), Citra Rasa (X2) and Promotion (X3) together have a positive and significant effect on Purchase Interest. Keywords: Effect of Product Quality, Taste Image, Promotion, Purchase Intention, Bay Tat Cake